Respuesta :
Answer:
a) The acceleration of the jogger is 1.5 m/s²
b) the acceleration of the car is also 1.5 m/s²
c) Yes, the car travels 76 m farther than the jogger.
Explanation:
a) The acceleration of an object is the variation of its velocity over time:
a = final velocity - initial velocity / time
for the jogger:
a = 3.0 m/s - 0 m/s / 2.0 s = 1.5 m/s ²
b) For the car:
a = 41.0 m/s - 38.0 m/s / 2.0 s = 1.5 m/s²
c) Let´s see the position of the car after 2 seconds.
The equation for the position of an accelerated object moving in a straight line is:
x = x0 + v0* t +1/2 * a * t²
Where:
x = position of the car at time "t"
x0 = initial position
v0 = initial velocity
t = time
a = acceleration
Let´s consider x0 = 0 because the origin of the reference system is located where the car starts accelerating. Then:
x = 38,0 m/s * 2 s + 1/2 * 1.5 m/s ² * (2.0 s)²
x = 79 m
In the same way, we can calculate the position of the jogger:
x = 0 m/s * t + 1/2 * 1.5 m/s ² * (2.0 s)²
x = 3 m
The car travels 79 m - 3 m = 76 m farther than the jogger
Answer:
(a) The acceleration of the jogger : [tex]$a_{j}=1.5 \mathrm{~m} \cdot \mathrm{s}^{-2}$[/tex]
(b) The acceleration of the car : [tex]$a_{c}=1.5 \mathrm{~m} \cdot \mathrm{s}^{-2}$[/tex]
(c) The car travel farther than the jogger during the [tex]2.0\ s[/tex] : [tex]$x_{c}-x_{j}=76 \mathrm{~m}$[/tex]
Explanation:
A jogger accelerates from rest to [tex]3.0 m/ s[/tex] in [tex]2.0\ s[/tex]
A car accelerates from [tex]38.0[/tex] to [tex]41.0 m/s[/tex] also in [tex]2.0 \ s[/tex]
Step 1:
Using the following equation of motion:
[tex]$v=v_{0}+a t$[/tex]
we can get the acceleration as:
[tex]$a=\frac{v-v_{0}}{t}$[/tex]
(a) If the jogger start from rest [tex]$v_{0}=0$[/tex] to a speed of [tex]$v=3 \mathrm{~m} \cdot \mathrm{s}^{-1}$[/tex] in time interval of [tex]$t=2 \mathrm{~s}$[/tex], the acceleration is:
[tex]$a_{j}=\frac{v-v_{0}}{t}$[/tex]
[tex]$=\frac{\left(3 \mathrm{~m} \cdot \mathrm{s}^{-1}\right)-(0)}{(2)}$[/tex]
[tex]&=1.5 \mathrm{~m} \cdot \mathrm{s}^{-2} \end{aligned}$[/tex]
Step 2:
(b) If the car start from the rest [tex]$v_{0}=38 \mathrm{~m} \cdot \mathrm{s}^{-1}$[/tex] to a speed of [tex]$v=41 \mathrm{~m} \cdot \mathrm{s}^{-1}$[/tex] in a time interval of [tex]$t=2 \mathrm{~s}$[/tex], the acceleration is:
[tex]$a_{c}=\frac{v-v_{0}}{t}$[/tex]
[tex]$=\frac{\left(41 \mathrm{~m} \cdot \mathrm{s}^{-1}\right)-\left(38 \mathrm{~m} \cdot \mathrm{s}^{-1}\right)}{(2)}$[/tex]
[tex]$=1.5 \mathrm{~m} \cdot \mathrm{s}^{-2}$[/tex]
Step 3:
Using the following equation we can calculate the distance:
[tex]$x=v_{0}+\frac{1}{2} a t^{2}$[/tex]
From the jogger,
[tex]$x_{j}=v_{0}+\frac{1}{2} a t^{2}$[/tex]
[tex]&=0+\frac{1}{2}\left(1.5 \mathrm{~m} \cdot \mathrm{s}^{-2}\right)(2 \mathrm{~s})^{2} \\[/tex]
[tex]&=3 \mathrm{~m} \end{aligned}$[/tex]
[tex]$x_{j}=4.5 \mathrm{~m}$[/tex]
Step 4:
For the car,
[tex]$x_{c}=v_{0} t+\frac{1}{2} a t^{2}$[/tex]
[tex]&=\left(38 \mathrm{~m} \cdot \mathrm{s}^{-1}\right)(2)+\frac{1}{2}\left(1.5 \mathrm{~m} \cdot \mathrm{s}^{-2}\right)(2 \mathrm{~s})^{2} \\[/tex]
[tex]&=79 \mathrm{~m} \end{aligned}$[/tex]
[tex]$x_{c}=79 \mathrm{~m}$[/tex]
Therefore, the car travles [tex]$x_{c}-x_{j}=76 \mathrm{~m}$[/tex] further than the jogger.
To learn more about acceleration, refer:
- https://brainly.in/question/6170540
- https://brainly.com/question/18672358